ORIGEM DO CARBONO INORGÂNICO DISSOLVIDO NO RIO TIETÊ (SÃO PAULO): REAÇÕES DE EQUILÍBRIO E VARIABILIDADE TEMPORAL - Mortatti, J.; Oliveira, H.; Bibian, J. P.; Lopes, R. A.; Bonassi, J. A.; Probst, J. L. (Geochimica Brasiliensis, 2012)